Revitalisasi Pengajaran Sejarah dan Upaya Menuju Profesionalisme Guru-Guru Sejarah - Soebijantoro, Soebijantoro (Jurnal Pendidikan, 2009)
Teaching of history is one out of that of other subjects in schools, which activity includes the implementation of nurturing societal values from one generation to another. Nurturing societal values to students in class can in turn empower their awareness of the past through a systematic learning design. Teachers of history should consequently understand their duty â not only carrying out the proper instructional design, but also nurturing those societal values to students. That duty can only be realized by developing both instructional strategy and value acquisition, so as to contribute as professional history teachers who implement the long life education.Key words : revitalization, teachersâ professionalism